Comparison of saftey and cost effectiveness of atorvastatin 40 mg daily, rosuvastatin 20 mg daily and rosuvastatin 20 mg alternate day in 300 patients with type 2 diabetes mellitus - Upadhyay, Durgesh Mani; Ahmad, Minhaz; Misra, Mukul; Chawdhary, Sandeep; Maurya, S. C. (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes is recognized as a “coronary heart disease risk equivalent”. This happens because high rates of dyslipidemia among diabetic patients which is thought to be one of the major factors leading to the high percentage of deaths among diabetics due to cardiovascular disease (CVD). Methods: The study aims to compare the cost effectiveness and tolerance or safety profile of atorvastatin 40 mg daily and rosuvastatin 20 mg daily and on alternate day. This prospective observational study was conducted in 300, type-2 diabetes mellitus patients between November 2013 and 2014. Results: The total CK level increased after 6 weeks among patients on atorvastatin 40 mg, rosuvastatin 20 mg, and rosuvastatin 20 mg alternate day was stastically significant although it was within accepted normal range. None of the patients reported to have muscle symptoms i.e. myalgia. SGOT, SGPT, bilirubin levels with atorvastatin 40 mg were statistically insignificant. Same was the case with rosuvastatin 20 mg daily. However the SGOT and bilrubin level increased with rosuvastatin 20 mg alternate day was statistically significant, but was within normal range, we attribute it to chance. The cost obviously has shown to half in rosuvastatin 20 mg on alternate day. Conclusions: Atorvastatin 40 mg, rosuvastatin 20 mg and rosuvastatin 20 mg alternate day was statically significant (p<.0010). SGOT, SGPT, bilirubin with atorvastatin 40 mg were statistically insignificant. Same was case with rosuvastatin 20 mg daily. SGOT, bilirubin level increased with rosuvastatin 20 mg alternate day was statistically significant. Cost obviously shown to half in rosuvastatin 20 mg alternate day.